A inserção do enfermeiro no time de resposta rápida nas unidades de internação - Abreu, Ana Rozelia Ramos de (Universidade do Vale do Rio dos Sinos, 2011)
This is a qualitative research study with a descriptive exploratory character. For the research in question was applied to approach interviews with focus group (Focus Group), which aims to evaluate the performance model of the rapid response team in a Private Hospital Institution for the care and risk reduction to the probable complications during this treatment period. Five nurses, six nursing technicians and four hospitalists doctors were recruited for the research. Data collection was performed through semi-structured interview, conducted during March and April 2012. The analysis of Bardin's content was used to verify the data analysis.The results obtained highlight the importance of discussing with team members the outcomes of care in the form of education, training. Investigating the clinical judgment of nurses, the very technical. Improving the performance of members of the Rapid Response Team on patient care of high complexity, in an emergency at the hospital.

Este es un salto cualitativo de carácter exploratorio descriptivo, donde se aplicó el enfoque de entrevistas a grupos focales (Focus Group), cuyo objetivo es evaluar el modelo de rendimiento del equipo de respuesta rápida para la reducción de riesgos y atención de la salud complicaciones probables a lo largo de cuidado. Las enfermeras del estudio, los técnicos de enfermería y médicos hospitalistas. La recolección de datos se realiza a través de entrevista semi-estructurada que utilizó el análisis de contenido de Bardin. Los resultados revelaron tres temas, con sus subtemas. Los resultados obtenidos muestran la importancia de discutir con miembros del equipo los resultados de la atención en la forma de educación y formación, está investigando el juicio clínico de las enfermeras, la mejora del rendimiento de los miembros del Equipo de Respuesta Rápida de la atención al paciente de alta complejidad en situaciones de emergencia en el hospital.
Keywords: Enfermagem; Time; Internação; Nursing; Team; Hospitalisation; Enfermería; El equipo; El hospital